PENYULUHAN PEMBELAJARAN BAHASA INDONESIA BERBASIS INTELEGENSI NATURAL PADA GURU PAUD NON FORMAL DI KECAMATAN GAYAMSARI SEMARANG - Harjito IKIP PGRI Semarang; Nazla Maharani Umaya; Ika Septiana; Ahmad Rifai; Sri Wijayanti (Universitas PGRI Semarang, 2011)
Abstract ?é?á A natural intelligence is a new method in the teaching and learning process in as the steps of indication to associate the needed subtance. It has a purpose to build the children?óÔé¼Ôäós intelligence to be multintellegence. This method is used to make an effective teaching learning process which deals with the students?óÔé¼Ôäó potential quality to get the maximal output in long term. This concept is actually presented to the early age learners in learning Bahasa Indonesia to know how their mother tongue will influence their second language based on the community that they live with. By living with their community who speaks Bahasa Indoensia as the second language, they will learn it in how to speak and write naturally. Learning Bahasa Indonesia using a natural intelegence is a good method in making them able to speak and write it well because this method motivate and force them how to understand, comprehend and apply it directly. And this method was actually trained to teachers of Non ?óÔé¼ÔÇ£ Formal PAUD / Under age /children group. By having this training, Non ?óÔé¼ÔÇ£ Formal PAUD teachers will be apble to implement the method well and the result will make children learn Bahasa Indonesia effectively and creatively. Key words : children?óÔé¼Ôäós intelegence, Bahasa Indonesia, Non ?óÔé¼ÔÇ£ Formal PAUD